Website Development As An Online Classroom For Online Classes In Distance Learning - Regina Halent; Ika Prasetya Mukti; Janu Pinardi (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2020)
The spread of COVID-19 outbreaks makes learning activities in Indonesia become online learning. Online learning is followed by new problems, those are limited internet data, bad internet networks, and the use of many applications. Online learning in Indonesia must be immediately optimized because the COVID-19 outbreak is not over yet and there is a discourse that online learning will be applied permanently. The teacher can optimize online learning by building a website as an online classroom. If teachers build their websites, they can adjust the features on the website based on the online learning problems and the subject matter needs. Based on a questionnaire distributed, 83% of student respondents agreed if the teacher made a website. Besides, most of teacher respondents think the website can optimize online learning. The idea of the website as an online classroom is expected to contribute ideas and alternatives for online learning programs in Indonesia.